Lived experience of medical management in recurrent vulvovaginal candidiasis: a qualitative study of an uncertain journey - Moira Bradfield Strydom; Ramesh L. Walpola; Sara McMillan; Sohil Khan; Robert S. Ware; Evelin Tiralongo (BMC, 2022)
Abstract Background Recurrent vulvovaginal candidiasis (RVVC) is experienced by up to 10% of pre-menopausal women globally, yet there is limited research exploring the perspective of women living with this challenging condition. Methods Semi-structured interviews with Australian women experiencing RVVC were conducted between April-July 2021. Interviews were transcribed verbatim, and qualitative interpretative phenomenological analysis (IPA) was conducted. Results Ten RVVC patients were interviewed. IPA revealed an uncertain journey living with RVVC for all participants ranging from initial symptoms and difficulties in obtaining a diagnosis, the trial and error of symptom management, to the overall debilitating impact of living with a personal and intimate health condition. Four key themes were identified: Theme 1 outlined challenges and delays in diagnosis and clinically appropriate management. Theme 2 found that health care professional (HCP) knowledge limitations impacted RVVC management. Theme 3 illustrated the consequences of a lack of HCP support leading to self-referral and self-education. Theme 4 details the significant emotional and psycho-social repercussions of RVVC. Conclusions This debilitating, life-long disease has a prolonged effect on women both physically and psychologically. Living with RVVC seems an uncertain journey that, to a large degree, women feel they must navigate alone. While resilience and self-empowerment were noted, better support through evidence-based treatment options, educated and evidence-informed HCPs and a sympathetic social support network is needed to decrease the disease burden. Future clinical management guidelines and patient support need to consider the findings of this study.